Clones de Eucalyptus versus a produção de polpa celulósica - Paulo Fernando Trugilho; Maria Lucia Bianchi; José Lívio Gomide; José Tarcísio Lima; Lourival Marin Mendes; Fábio Akira Mori; Débora De Faria Ferreira Gomes (Ciência Florestal, 2005)
The wood quality is defined by combining several intrinsic characteristics of the tree to its use. This research aimed to evaluate some of the wood characteristics of Eucalyptus clones and its performance in kraft pulping. Fifteen clones, 5.8 years-old were used, two trees from each clone, totaling thirty trees. The evaluated wood characteristics were: basic density, fiber dimensions (fiber length, wall thickness, lumen diameter) and chemical composition (cellulose, lignin, hemicelluloses, extractives and ash contents). Four samples were cooked at the laboratory for each tree, using different active alkali, to establish the delignification curve. These alkali loads were selected after exploratory cooking to obtain an eighteen kappa number at the medium point of the curve. In the cooking were appraised the screened, the pulp viscosity and consumed alkali. The yield results varied from 43.4 to 52.0%, the active alkali from 17.5 to 23.4%, the consumed alkali from 15.5 to 20.0% and the pulp viscosity from 19.9 to 61.4 cP.